Invariant and reversible measures for random walks on Z - Rivasplata Zevallos, Omar; Schmuland, Byron (Pontificia Universidad Católica del Perú, 2005)
In this expository paper we study the stationary measures of a stochastic process called nearest neighbor random walk on Z, and further we describe conditions for these measures to have the stronger property of reversibility. We consider both the cases of symmetric and non-symmetric random walk.
Keywords: Random Walk; Invariant Measure; Reversible Measure; https://purl.org/pe-repo/ocde/ford#1.01.00